Gelation of Novel Pyrene‐Cored Chiral Dendrimers: Dendritic Effect in Gelation and Shear Thinning Behavior. Issue 1 (November 2016) - Bhattacharjee, Subham; Maiti, Bappa; Biswakarma, Dipen; Bhattacharya, Santanu
Summary: Synthesis and gelation property of novel pyrene‐cored chiral dendrimers PyFG1 and PyFG2 have been studied. Dendritic effect was found to play a crucial role in the self‐assembly pattern, solvents for gelation and the shear thinning behavior of the gels as well.